الفتوى في مجال السّياسة الشّرعيّة, موجباتها, ضوابطها وتطبيقاتها - عباسي, أحمد المبارك (جامعة الوادي - University of Eloued, 2021)
تتطرق هذه الورقة البحثيّة لموضوع تغير الفتوى في مجال السّياسة الشّرعيّة في الإسلام, وتتناول مفهوم الفتوى والمفتي, والمراد منهما في اللغة والاصطلاح, والشّروط والصّفات التي ينبغي مراعاتها في مَن يتصدّى لهذه المهمة النّبيلة, وكذا تعريف السّياسة الشّرعيّة والمراد منها عند الإطلاق, ومدى أهمية الفتوى في هذا المجال, وبيان خطورتها أيضا لأنّها تتعلق بأمور ترتبط ارتباطا وثيقا بكيان الأمّة الإسلاميّة. لتبحث بعدها مسألة تغير الفتوى والمقصود منها, ثمّ تعالج بعض الموجبات التي وضعها الفقهاء لتغير الفتوى بتغير الزّمان والأحوال, والضّوابط والشّروط التي تحكم هذا التّغير، وتتناول أيضا بعض النّماذج والصّور لفتاوى في باب السّياسة الشّرعيّة. وخلُص البحث في الأخير إلى جملة من النّتائج والاقتراحات حول تنظيم مسألة الفتوى, وعدم ترك المجال لأصحاب الأهواء وقليلي العلم لتصدّر السّاحة والإفتاء بغير علم. وقد اتبعت في هذا البحث المنهج الاستقرائي وذلك بتتبع الآيات والأحاديث التي تخدم البحث, وكذا المنهج التحليلي, لتحليل الآراء الفقهية ومناقشتها وترجيح أحدها على الأخر. وقد نهجنا المنهج الوصفي بالنّسبة للمفاهيم والحقائق. This research paper deals with the topic of changing the fatwa in the field of Sharia policy in Islam, and deals with the concept of the fatwa and the mufti, what is meant in language and convention, the conditions and characteristics that should be observed in those who stand up to this noble task, as well as the definition of the legal policy and what is intended at launch, and the importance of the fatwa in This field, and also indicating its danger, because it is related to matters closely related to the existence of the Islamic nation. Then it discusses the issue of changing the fatwa and what is meant by it, then it deals with some of the obligations that the jurists have set for changing the fatwa by changing time and conditions, and the controls and conditions that govern this change, and also deals with some models and images of fatwas in the section on Sharia policy. Finally, the research concluded with a set of results and suggestions regarding organizing the issue of fatwa, and not leaving the space for those with whims and little knowledge to lead the arena and fatwas without knowledge. In this research, I followed the inductive approach by following the verses and hadiths that serve the research, as well as the analytical method, to analyze and discuss the jurisprudential opinions and weight one of them over the other. We have taken a descriptive approach to concepts and facts.
مقال
Keywords: لفتوى؛ المفتي؛ صناعة الفتوى؛ السياسة الشرعية؛ الموجبات; key words: Fatwa؛Mufti؛ Fatwa industry؛ islamic policy؛ The obligations